2022
DOI: 10.3390/ijerph19074027
|View full text |Cite
|
Sign up to set email alerts
|

Positive Health Behavior Changes in Custodial Grandparents and Grandchildren Following an Intervention

Abstract: Background: Custodial grandparents experience greater physical health declines and higher rates of depression than their same-age peers who do not provide care, and grandchildren in grandfamilies often have behavior problems. However, few researchers have explored the impact of self-care education on decreasing these negative outcomes. Our study examined how a self-care and life-skills intervention influenced health behavior change in a sample of grandparents and grandchildren. Methods: Data were collected dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Carrere et al revealed that a communal or cooperative family structure could enhance health and well-being mediated by psychosocial determinants of health 36 . In contrast, the grandparent-headed family structure appears to lead to greater physical health declines and higher rates of depression among grandparents caring for grandchildren than their peers who are not primary caregivers of grandchildren 37 . Although studies suggest that caring for grandchildren in a grandparent-headed family structure can negatively affect grandparents' health, Rapoport et al observed that grandparents who care for their children seem to cope with parenting just as well as parents 18 .…”
Section: The Reflects Of Changes In the Family Structure On Healthmentioning
confidence: 88%
“…Carrere et al revealed that a communal or cooperative family structure could enhance health and well-being mediated by psychosocial determinants of health 36 . In contrast, the grandparent-headed family structure appears to lead to greater physical health declines and higher rates of depression among grandparents caring for grandchildren than their peers who are not primary caregivers of grandchildren 37 . Although studies suggest that caring for grandchildren in a grandparent-headed family structure can negatively affect grandparents' health, Rapoport et al observed that grandparents who care for their children seem to cope with parenting just as well as parents 18 .…”
Section: The Reflects Of Changes In the Family Structure On Healthmentioning
confidence: 88%
“…For example, Ruiz's study (2008) used focus groups [53], while Dolbin-MacNab et al's study (2021) [54] and Lee et al's study (2015) [55] used interviews. Marken et al's study (2010) utilized both interviews and videos [56], three studies combined focus groups and interviews [57][58][59], and two studies used alternative data collection methods such as the photovoice methodology [60] and interaction reports from help lines [61]. All the three mixed method articles [62][63][64] used descriptive data analysis to describe the sample, and qualitative data analysis to explore the factors contributing to kinship caregivers' resilience.…”
Section: Research Designsmentioning
confidence: 99%
“…Additionally, kinship caregivers used other methods such as having shared festive leisure with the children to manage their stress, which further brought benefits for them, including increased creativity, improved physical condition, happiness, better relationship with children, and new manual and technical skills [46,58]. Fox et al (2022) developed an intervention aimed at improving kinship caregivers' self-care skills [47]. Fox et al (2022) and Fruhauf et al (2022) found that when using self-care to cope with stress, caregiver's self-efficacy improved [47,58].…”
Section: Coping Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of effective communication may further intensify conflicts and their consequences (Hoang et al, 2020). Most studies have found that children raised mainly by grandparents tend to report deteriorating health compared with those cared for by parents (Fan et al, 2010; Hong & Zeng, 2022; Joshi & Lebrun‐Harris, 2022; Liu et al, 2018; Pilkauskas & Dunifon, 2016; Ruiz & Silverstein, 2007; Xu et al, 2022), but exceptions have also been documented (Fruhauf et al, 2022; Pong & Chen, 2010; Tanskanen & Danielsbacka, 2017). For example, a cross‐sectional study conducted in Taiwan reported that children mainly cared for by grandparents achieved higher cognitive scores (Pong & Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%